Salivary gland adenocarcinoma in an orange-spined hairy dwarf porcupine (Sphiggurus villosus) - Perles, Lívia [UNESP]; Kawamoto, Fernando Y. K. [UNESP]; Matsui, Andresa [UNESP]; Ribeiro, Julia M. [UNESP]; Vasconcelos, Rosemeri de O. [UNESP]; Werther, Karin [UNESP] (Brazilian Journal of Veterinary Pathology, 2017)
The goal of this case report is to describe a salivary gland adenocarcinoma in a free ranging Sphiggurus villosus. A orange-spined hairy dwarf porcupine (S. villosus) was referred to the Wildlife Medicine Service at the Veterinarian Hospital of the Universidade Estadual Paulista (Jaboticabal, São Paulo, Brazil), with a mass in the lateral region of the face. Radiographs highlighted swelling in the soft tissues, measuring 7 cm x 9 cm, without bone involvement. The physical examination and radiographs were consistent with a neoplastic process. The animal was submitted to surgical excision of the mass. Microscopically, the tumor was composed of a highly cellular proliferation of epithelial cells arranged predominantly in tubular pattern, associated with moderated fibrous stroma, poorly demarcated, non-encapsulated and with infiltrative growth. These findings were consistent with salivary gland adenocarcinoma. To the authors’ knowledge, this is the first report of a salivary gland adenocarcinoma in a wild life orange-spined hairy dwarf porcupine.
Keywords: Clinical-histological diagnostic; Neoplasia; Rodentia; Surgery; Wildlife